A Quasi‐Solid Electrolyte by In Situ Polymerization of Selective Solvent for Lithium‐Metal Batteries. Issue 24 (15th December 2022) - Wang, Jin; Tao, Chengzhou; Cao, Jiaming; Jiao, Xiaoxia; Wang, Lina; Liu, Tianxi
Abstract: Lithium (Li) metal is a competitive anode material for rechargeable high energy density batteries due to its high specific capacity and low reduction potential. However, great challenges remain in addressing uncontrollable Li dendrite growth and unstable interface. Herein, we report a quasi‐solid electrolyte enabled by in situ polymerization of polyethylene glycol methyl ether acrylate. Meanwhile, a LiF‐enriched solid electrolyte interphase (SEI) is built on Li‐metal surface by function of the fluoroethylene carbonate additive. The SEI with a good mechanical stability prompts the dense and uniform Li deposition behavior. The in situ polymerized gel polymer electrolyte exhibits an ionic conductivity of 1.71×10 −4  S cm −1 at 30 °C, and a considerable oxidative stability up to 4.5 V (vs. Li/Li + ). The Li||Li symmetric cells delivers a long‐term cycle life over 1400 h and a low voltage hysteresis at 0.5 mA cm −2, 1 mAh cm −2 . To be paired with a LiFePO4 positive electrode, the cell shows a high discharge capacity of 135.6 mAh g −1 and capacity retention of 92.7 % after 300 cycles. This work provides a reference for the practical development of quasi‐solid electrolyte for lithium‐metal battery. Abstract : A viable quasi‐solid electrolyte by an in situ polymerization process of polyethylene glycol methyl ether acrylate for Li‐metal batteries is demonstrated, and the LiF‐rich solid electrolyte interphase is simultaneously constructed to suppress the growth of lithium dendrites.